Driving Green Product Purchase Intention through the Elaboration Likelihood Model: The Roles of Para-Social Interaction and Information Quality in Live-Streaming E-Commerce - Prananta, Widya; Prihandono, Dorojatun; Wiratama, Bayu; Febriatmoko, Bogy; Dwi Praatmana, Nanang (Management Analysis Journal, 2025)
This study examines how Information Quality and Para-Social Interaction influence Green Product Purchase Intention in live-streaming e-commerce using the Elaboration Likelihood Model (ELM). Driven by rising sustainable consumption trends, it explores their impact through Subjective Product Knowledge as a mediator, extending ELM by integrating cognitive and affective cues in Indonesia’s growing digital market. Data were collected from 140 young consumers (aged 17–37) in Semarang, Indonesia, who engage in live-streaming e-commerce. The analysis tested hypotheses, revealing that Information Quality enhances Subjective Product Knowledge, which drives purchase intention, while Para-Social Interaction directly and indirectly affects both. Subjective Product Knowledge mediates these relationships. This offers a novel application of ELM in sustainable consumer behavior in de-veloping countries. Practically, businesses can use high-quality information and trusted streamers to boost green product sales in global markets.